Low awareness and common misconceptions about schistosomiasis in endemic lowland areas in Western Ethiopia: a mixed-methods study - Alemayehu Assefa; Berhanu Erko; Svein Gunnar Gundersen; Girmay Medhin; Nega Berhe (BMC, 2021)
Abstract Background Understanding the health behavior of the target population is crucial for sustainable schistosomiasis control. The aim of this study was to assess schistosomiasis related levels of knowledge, attitude, and practices of communities in lowland areas of western Ethiopia, where schistosomiasis is endemic. Methods A community-based multilevel triangulation mixed-methods design was conducted in three schistosomiasis endemic villages in the Abbey and Didessa valleys of the Benishangul Gumuz Region of Western Ethiopia, where mass drug administration (MDA) was done 30 years back and again the last 5 years. A structured survey questionnaire, in-depth interviews, focused group discussions, and observation was conducted to assess levels of knowledge, attitude, and practices related to schistosomiasis in the communities. Results Among the survey participants, 13% reported having heard of schistosomiasis, locally called Pecka (meaning worm). The majority of this 13% believe that schistosomiasis is caused by the biting of the worm Pecka, while others say drinking dirty water is the cause of infection, or they didn't know what the cause is. A majority of respondents answered "I don't know" to most of the questions about established knowledge of schistosomiasis. Male participants and students were more aware of schistosomiasis than their counterparts, and awareness increased with the educational level. Only one participant perceived that schistosomiasis was a serious disease. There were negative attitudes and misconceptions about the drug used in the mass treatment and many complaints were raised related to the size of the tablet and its side effects. There was no local budget and specific plan to prevent and control the disease. Local health personnel had insufficient knowledge about schistosomiasis, and the diagnosis and treatment capacities of local health institutions were poor. Conclusion In the current research area, schistosomiasis prevention and control recommendations should be redesigned to change the knowledge, attitudes, and practices of the community and local health workers. It is also necessary to have the local budget and trained manpower in order to diagnose and treat schistosomiasis locally. There is a great need to have a safer Praziquantel pediatric formulation.